A technique to prevent recurrence after the repair of pacemaker lead-induced tricuspid regurgitation. (25th January 2019) - Kitamura, Hideki; Koyama, Yutaka; Tamaki, Mototsugu; Sawada, Koshi
Abstract: This article describes how to repair pacemaker lead-induced tricuspid regurgitation without removing the pacing leads. Our technique can eliminate the lead contact with the tricuspid leaflets and the tricuspid apparatus and is effective in preventing recurrence.